Application of rock phosphate enriched composts increases nodulation, growth and yield of chickpea - Allah Ditta; Juma Muhammad; Muhammad Imtiaz; Sajid Mehmood; Zheng Qian; Shuxin Tu (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose Phosphorus (P) deficiency in agricultural land is one of the main factors which reduce the crop production and yield. To increase the crop growth, the availability of P using the rock phosphate (RP) can be enhanced using organic waste with the addition of phosphate solubilizing microorganisms (PSMs). Moreover, the combination along with time and dose application of RP and compost can also affect the P-availability through mineralization and/immobilization. Methods To investigate the effect of different combinations of RP and compost (0:100, 25:75, 50:50, 75:25 and 100:0) and time of application (30, 15, 7, 3 and 0 days before sowing), each was conducted in two consecutive pot experiments while, the rate of application (100–1000 kg ha−1) was investigated under field conditions, in comparison to control (recommended P fertilizer). Results Rock phosphate enriched compost (RP-EC) with a combination ratio of 50:50; RP and compost applied before 7 days of sowing in pot experiments resulted in the maximum nodulation, growth and productivity of chickpea. Under field conditions, the maximum increase of 35.3% in no. nodules plant−1, 26.7% in dry wt. of nodules plant−1 and 20.8% in grain yield (t ha−1) compared to control was obtained by RP-EC @ 1000 kg ha−1. The same treatment indicated an increase of 12.9 and 4.3% in P contents in straw and grains, respectively, compared to control. However, most results were non-significant when RP-EC applied at the rate of 1000 kg ha−1. Conclusion Application of RP-EC, with the ratio of 50:50 (RP:Compost) and application rate of 800 kg ha−1 before 7 days of sowing, exhibited maximum growth and development, and can be highly recommended for optimum production of chickpea.